'Calling to witness: complicating autobiography and narrative empathy in Marlon Riggs's Tongues Untied'. Issue 1 (2nd January 2019) - Anderst, Leah
ABSTRACT: This article focuses on Tongues Untied, Marlon Riggs's 1989 documentary whose aim is to give voice to the diverse experiences of black gay men in the late 1980s, at the height of the AIDS crisis. I examine Riggs's use of autobiographical storytelling and argue that his visual and rhetorical strategies during these moments evince the filmmaker's hesitation to become his own subject and to allow viewers into his experiences. In other words, the formal strategies adopted during the autobiographical sequences complicate narrative empathy. The authorship of one's own identity is an important thread in Tongues Untied, and empathetic responses may be in part a desire in viewers to participate in the authoring of or colonizing of Riggs's represented identity. I argue that the film resists this, and, while it remains a call to witness, it is, then, a critique of viewers' desire for narrative empathy..